2016
DOI: 10.1007/s00766-016-0259-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous clarification and emergent requirements flows in open-commercial software ecosystems

Abstract: Software engineering practice has shifted from the development of products in closed environments toward more open and collaborative efforts. Software development has become significantly interdependent with other systems (e.g. services, apps) and typically takes place within large ecosystems of networked communities of stakeholder organizations. Such software ecosystems promise increased innovation power and support for consumer-oriented software services at scale and are characterized by a certain openness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 53 publications
0
24
0
13
Order By: Relevance
“…We base our discussion on an industrial study manner [46], which is effective and natural. Yet, the difficulty with this manner is in the control of the top down decomposition [28].…”
Section: Practical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We base our discussion on an industrial study manner [46], which is effective and natural. Yet, the difficulty with this manner is in the control of the top down decomposition [28].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…We have seen in Section 5 of the paper that our approach Knauss et al [28] suggested that early involvement of stakeholders in requirements elicitation is crucial in ensuring the success of collaborative systems. Our approach addresses this challenge by asking the stakeholders a set of questions about the system context.…”
Section: Addressing Re Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, however, research has so far mainly investigated emergent developers [14,31,42] and emergent knowledge [46], while only few and more recent works exist that start to investigate the effect of emergent contributors on requirements [26], across organizations [24,28], and its implications with respect to transparency [8,15]. We consider this an important research direction, since stakeholders with in-depth domain knowledge, the implicit knowledge about customer needs, their business domain and the system's environment [9], must participate even when they span team-or geographic boundaries [5].…”
Section: Related Workmentioning
confidence: 99%